تصميم المواد الدراسية في تعليم المهارات اللغوية الأربع - Ana Achoita (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2019)
Arabic has four elements of skill, namely listening, speaking, reading and writing. In teaching the four language skills it is needed appropriate teaching material so that students are able to master the language skills they pursue and students can play an active roles in building knowledge and their involvement in teaching and learning. So that teachning materials is needed in accordance with the principles of language skills, and it is prepared according to right procedures as well as their arrangement principles, namely: language, culture and education besides teaching methods.